2016
DOI: 10.1016/j.foodpol.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agricultural interventions on the nutritional status in South Asia: A review

Abstract: HighlightsHome production of targeted crops for nutrients intake and nutritional outcomes.Homestead gardens for improved diet diversity.Diversification of agriculture for improved diet diversity and nutritional outcomes.No conclusive evidence of impact of irrigation on diet diversity.Empowerment of women crucial for improving nutritional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 23 publications
7
111
0
3
Order By: Relevance
“…More specifically, the expansion of carbohydrate production may have alleviated immediate hunger, but the nutrition of the population is still found wanting due to the absence of sufficient diversity in diets. Greater diversity in production is a seen as one panacea (e.g., [28]).…”
Section: The Underpinnings Of Scarcity and Equitable Water Distributimentioning
confidence: 99%
“…More specifically, the expansion of carbohydrate production may have alleviated immediate hunger, but the nutrition of the population is still found wanting due to the absence of sufficient diversity in diets. Greater diversity in production is a seen as one panacea (e.g., [28]).…”
Section: The Underpinnings Of Scarcity and Equitable Water Distributimentioning
confidence: 99%
“…Our findings are in line with earlier findings from reviews (Masset et al 2012;Girard et al 2012) that suggest there is limited evidence of agricultural interventions having significant positive impacts on child nutrition. Other studies (Berti et al 2004;Pandey et al 2016) found that without additional programming in other areas relevant for positive nutrition outcomes, such as gender or nutrition, agricultural programs are unlikely to have a significant positive impact on nutrition. The N2Africa project did include training on soya processing and targeted inclusion of 50% female participants but during the first phase did not include nutrition-specific training or other genderrelated interventions.…”
Section: N2africa and Children's Nutrition Outcomesmentioning
confidence: 99%
“…• Agriculture-nutrition linkages Several studies have analyzed the ways in which agriculture can be leveraged to enhance nutritional outcomes (Pandey, Dev, and Jayachandran 2016). The strong association between agricultural interventions and nutritional status through the production of targeted nutritionrich crops, homestead gardens, and diversification of the agricultural production system toward fruits and vegetables and aquaculture supports improving nutrient intake and nutritional outcomes.…”
Section: Intervention Optionsmentioning
confidence: 99%